Evaluation of geriatric trauma in dogs with moderate to severe injury (6169 cases): A VetCOT registry study. Issue 3 (7th February 2022) - Young, Anda A.; Cooper, Edward; Yaxley, Page; Habing, Greg
Abstract: Objective: To examine geriatric classification as a predictor of survival in moderate to severely injured dogs denoted by animal trauma triage (ATT) scores ≥3 or modified Glasgow Coma Scale (mGCS) scores ≤14. Design: Retrospective observational cohort study utilizing data collected between September 2013 and May 2019 with follow‐up until death or hospital discharge. Setting: Thirty‐one trauma centers including university teaching hospitals and private referral centers. Animals: A total of 6169 dogs entered into the Veterinary Committee on Trauma Registry with complete data entry including age, weight, outcome, mGCS (≤14), and/or ATT (≥3). Interventions: None. Measurements and Main Results: The effect of geriatric classification on survival was estimated using shared‐frailty cox proportional hazard models. Model 1 dependent variables: death despite intervention or euthanasia due to grave prognosis. Model 2 dependent variables: death by euthanasia due to financial influence or combined influence of finances and grave prognosis. Model 3 evaluated interactions between geriatric classification and moderate versus severe trauma. The shared‐frailty models controlled for contributing site as a random effect and other confounding variables, including trauma severity. Model 1: geriatrics had a significantly increased hazard risk (HR) for death (HR = 1.48, P  < 0.0001). Model 2: geriatrics had an insignificant increased HR for death (HR = 1.34, P  = 0.08). Model 3: geriatrics demonstrated significantly increased mortality risk with moderate level trauma. Additional Model 1 variables independently associated with mortality include ATT perfusion, neurologic, respiratory subscores, mGCS motor subscore, weight, and spinal trauma. Additional Model 2 variables independently associated with mortality include ATT perfusion subscore and neuter status. In general, statistical differences between cohorts were found with regard to lactate, PCV, total protein, and glucose. Conclusions: Among moderately injured dogs who experienced death despite intervention or euthanasia due to grave prognosis, mortality risk is significantly higher in geriatrics as compared to nongeriatrics.